How to use graphic design to sell things, explain things, make things look better, make people laugh, make people cry, and (every once in a while) change the world - Bierut, Michael (High Holborn, London Thames & Hudson, 2015)
"Logos, packages, signs, publications, websites: in the modern world we are surrounded by graphic design. Where does it come from? Why does it look that way? What is it supposed to do? How to use graphic design to sell things, explain things, make things look better, make people laugh, make people cry, and (every once in a while) change the world is the first career monograph from graphic designer Michael Bierut. Using examples from a portfolio spanning five decades, Bierut provides the answers, describing three dozen projects from start to finish, with insights into creative process, his working life, his relationship with clients, and the challenges that any creative person faces in bringing innovative work into the world today"--Provided by publisher.
How to be a graphic designer in the middle of nowhere -- How to think with your hands -- How to destroy the world with graphic design -- How to have an idea -- How to create identity without logo -- How to invent a town that was always there -- How to work for free -- How to raise a billion dollars -- How to win a close game -- How to be good -- How to run a marathon -- How to avoid the obvious -- How to avoid doomsday -- How to be fashionably timeless -- How to cross cultures -- How to behave in church -- How to disorient an architect -- How to make a museum mad -- How to judge a book -- How to make mark -- How to squash a vote -- How to travel through time -- How to pack for a long flight -- How to have fun with a brown cardboard box -- How to shut up and listen - How to top the charts -- How to convince people -- How to get where you want to be -- How to investigate a murder -- How to be who you are -- How to get the passion back -- How to make news -- How to set a table -- How to survive on an island -- How to design two dozen logos at once -- How to save the world with graphic design
Keywords: Graphic arts -- Study and teaching; Graphic arts -- Technique; Graphic arts -- Marketing